Regulatory Tipping Point: Key Lessons from a Divergence in AI Regulation Between the EU and the US (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
In the last five years, artificial intelligence technologies have exploded onto the global stage. At the same time, different regions have drastically diverged in the approach to regulating artificial intelligence. This article explores two dominate players in the artificial intelligence world: the European Union and the United States, and discusses, in turn, how each has approached regulating artificial intelligence and lessons learned for the next wave of artificial intelligence development and regulation.